English Speaking Fluency and Confidence for Global Competitive Work: The Highlight of Authentic Role-play Activity for University Students - Ni Putu Intan Permatasari; Cok Istri Sri Agung Wulandari (Jurnal Multidisiplin Sahombu, 2025)
English language is increasingly important for many people around the world to engage and communicate with one another as the globe quickly transitions to the new era of digitalization and limitless communication. The study explores the descriptive elaboration and deeper understanding on the use of role-playing activities to boost students’ fluency and confidence in English speaking among university students. The study used a descriptive qualitative method which applicated various methods to collect the data. The present study employed class observation on speaking indicators, analysis on students’ reflective learning journal, and a semi-structured interview to some students. Thematic analysis was used to identify key themes that emerged from the data. There were 50 students observed and 10 students in English for communication class at Universitas Pendidikan Nasional, were interviewed to confirm about the highlighted aspects journaling related to the specific aspect on role-play activities. The findings of this study highlight the impact of role-playing activities on improving students’ fluency in English speaking, enhancing students’ confidence through repeated practice, and reducing the speaking anxiety to be ready for the global competitive English skill.